RICE QUALITY EVALUATION AS A FUNCTION OF CULTIVAR AND COOKING TIME - ASCHERI, Diego Palmiro Ramirez; PEREIRA, Luciane Dias; BASSINELLO, Priscila Zaczuk; CARVALHO, Carlos Wanderlei Piler; ASCHERI, José Luís Ramírez (Scientia Agraria, 2009)
Was studied the effects caused by the cultivar and cooking time on grain quality of five cultivars of upland rice (BRS Primavera, BRS Pepita, BRS Sertaneja, BRS Monarca and BRS MG Curinga) that were cooked at different cooking times (0, 10, 20, 30 and 40 min). The identified water content, starch and amylose, high viscosity and tendency to retrogradation and cooking tests were performed (yield, stickiness and texture). The results showed that the longer the cooking time the greater the availability of the contents of starch and amylose for their determinations and their values differ among cultivars of upland rice. Synergism was observed between the factors studied, increasing the water content and decreasing the maximum viscosity and the tendency to retrogradation with increased cooking time has been noted that cultivars BRS Pepita and BRS MG Curinga can absorb more water when they are hot and presented more stickiness when is cold and cultivars BRS Primavera, BRS Sertaneja and BRS Monarca can absorb minor water when they are hot and can be show dry grains and singles and harden after cooling.